(untitled) (OCEM Journal of Management, Technology & Social Sciences, 2026)
Customer satisfaction plays a crucial role in business success. Hoteliers have a difficult task in ensuring high customer satisfaction levels due to stiff competition and the complexity of meeting ever-changing contemporary customer needs, tastes, and preferences. This study’s main purpose was to determine the factors that influence the satisfaction of contemporary customers in the hotel industry. A quantitative research approach, following the descriptive research design, was used to conduct the study. A questionnaire-based survey methodology was used to collect data. One hundred and ten (N = 110) customers provided feedback by filling out the questionnaire and submitting it on time. Data analysis involved descriptive statistics in establishing the degree of impact of several factors on customer satisfaction. Value, money, and service quality are the leading factors that influence customer satisfaction. Location and price have a minimal but considerable impact on customer satisfaction. The quality of food and related services, including the availability of complementary services and staff attitude and behavior, affects customers’ perceptions of service quality. Value for money and service quality are the primary factors influencing customers’ satisfaction in the hotel industry. Hoteliers should invest in delivering optimal value to customers through high-quality services while meeting customer needs holistically.